A high performance sulfur-doped disordered carbon anode for sodium ion batteries. Issue 10 (24th August 2015) - Li, Wei; Zhou, Min; Li, Haomiao; Wang, Kangli; Cheng, Shijie; Jiang, Kai
Abstract : Sulfur-doped disordered carbon exhibits high capacity and excellent cyclability as an anode for sodium ion batteries. Abstract : Sulfur-doped disordered carbon is facilely synthesized and investigated as an anode for sodium ion batteries. Benefiting from the high sulfur doping (∼26.9 wt%), it demonstrates a high reversible capacity of 516 mA h g −1, excellent rate capability as well as superior cycling stability (271 mA h g −1 at 1 A g −1 after 1000 cycles).